Enhancing the Student Involvement in Learning Speaking through Impressive Personal Experience Material (IPEM) - Hasna Hasna (Universitas Nahdlatul Ulama Blitar, 2021)
Based on the observation in some speaking classes in Indonesia, most of the students reluctant to involve themselves in speaking learning process. Therefore, the study is aimed to find out: (1) the extent to which the influence of IPEM in making the students involve themselves in learning Speaking; and (2) the students’ interest in attending the Speaking class through IPEM. Students’ activities were observed, recorded, and noted during the teaching and learning process; and given questionnaires and interview in the last meeting in the class. The results show that: (1) IPEM enhances the student involvement in learning Speaking especially for most of those who get low involvement (33.3%) can achieve moderate involvement (56.7%); and (2) most of the students are interested in attending the Speaking class in which 89.6% of them are categorized high interested and the mean score of students’ questionnaire answer is 82 which is categorized high interested.